Skill Oriented Preventive Strategies and Eccentric Muscle Training on Shoulder Pain and Function in Volleyball Players with Shoulder Injury - An Experimental Study - Suryaprakash, Nagaraj; Manor Abraham, Manoharlal (INTI International University, 2023)
Background: Volleyball is a game which played by all age group in all over the world. In competitive atmosphere the collegiate players tend to get injuries, and the main considerable factor is these injuries are cumulative. Trained athletes also get cumulative injuries but prevalence of these kind of injuries are more in collegiate players because of improper skills and lack of adequate training, this study used to concentrate on correcting the skill as well as giving appropriate training. Method: This is an Experimental study; participants are 22 collegiate volleyball players from KG campus. They have divided into two groups by simple random sampling. Group A consist of 11 players. Group B consist of 11 players. Group A have received Eccentric muscle training along with skill oriented preventive strategies and Group B received Eccentric muscle training alone. After the acute management and rest, Eccentric muscle training and improving the skill by proper analysis and correction get started, duration of the study was 8 weeks. Results: The two outcome measures Spiking velocity and SPADI (shoulder pain and disability index) was used. Both Pain and activities shows positive improvement, t values of SPADI and Spiking Velocity is 11.731 and 2.765 at p<0.05. Conclusion: Eccentric muscle training along with skill oriented preventive strategies are help full in preventing the injuries as well improving the performance of an athlete.